Evaluation of GABAergic Transmission Modulation as a Novel Functional Target for Management of Multiple Sclerosis: Exploring Inhibitory Effect of GABA on Glutamate-Mediated Excitotoxicity - Ankit A. Gilani; Ranjeet Prasad Dash; Mehul N. Jivrajani; Sandeep Kumar Thakur; Manish Nivsarkar (Advances in Pharmacological Sciences)
Multiple sclerosis (MS) is an autoimmune inflammatory disease of the central nervous system (CNS) where the communication ability of nerve cells in the brain and spinal cord with each other gets impaired. Some current findings suggest the role of glutamate excitotoxicity in the development and progression of MS. An excess release of glutamate leads to the activation of ionotropic and metabotropic receptors, thus resulting in accumulation of toxic cytoplasmic Ca2+ and cell death. However, it has been observed that gamma-aminobutyric acid-A (GABAA) receptors located in the nerve terminals activate presynaptic Ca2+/calmodulin-dependent signaling to inhibit depolarization-evoked Ca2+ influx and glutamate release from isolated nerve terminals, which suggest a potential implication of GABAA receptor in management of MS. With this proof of concept, we tried to explore the potential of selective GABAA receptor agonists or positive allosteric modulators (diazepam and phenobarbitone sodium) and GABAA level enhancer (sodium valproate) for management of MS by screening them for their activity in experimental autoimmune encephalomyelitis (EAE) model in rats and cuprizone-induced demyelination model in mice. In this study, sodium valproate was found to show the best activity in the animal models whereas phenobarbitone sodium showed moderate activity. However, diazepam was found to be ineffective.